Porphyrin-functionalised rotaxanes for anion recognition. - Brown, A; Beer, P (2012)
The synthesis and anion-recognition properties of two new porphyrin-functionalised [2]rotaxane host molecules are described. The rotaxane compounds are prepared via a chloride-anion-templated clipping strategy. (1)H NMR titration experiments demonstrate that the rotaxane host systems exhibit high binding affinities and general selectivities for chloride anions in DMSO-d(6) or CDCl(3)/CD(3)OD solvent systems. UV-visible and fluorescence spectroscopy experiments reveal that the rotaxane receptors are ineffective as optical anion sensors. However, both receptors are shown to be capable of detecting chloride anions electrochemically via cathodic shifts in the porphyrin P/P(+) redox couples.